A modern review of uveal melanoma: molecular insights, clinical management, and emerging therapies - Bhanupriya Dhabhai; Abhijit Beura; Janvi Bhatankar; Arisha Imam; Narendra Kumar Sharma; Anita Rana; Amit Sharma; Pawan Kumar Maurya; Ingo GH Schmidt-Wolf; Abhishek Kumar; Tikam Chand Dakal (Melanoma Research, 2026)
Uveal melanoma is the most frequent primary intraocular malignancy in adults and is characterized by an aggressive clinical course, high propensity for hepatic metastasis, and poor survival after metastatic progression. Improvements in ocular imaging and local therapies have improved primary tumor control, but approximately half of patients will ultimately develop metastatic disease with poor treatment options. Recent advances in genomics and molecular biology have dramatically improved our understanding of uveal melanoma pathogenesis, with the discovery of activating mutations in GNAQ , GNA11 , CYSLTR2 , and PLCB4 as early oncogenic events that drive aberrant signaling through the protein kinase C (PKC), MAPK, PI3K/AKT, and Hippo–YAP pathways. Additional changes in BAP1 , SF3B1 , and EIF1AX as well as common chromosomal aberrations, contribute to tumor progression, metastatic risk and clinical heterogeneity. New insights into the distinct immune landscape of uveal melanoma, including low tumor mutational burden, immune-desert and immune-excluded phenotypes, a macrophage-dominant microenvironment, and hepatic immune tolerance, have provided important explanations for its poor response to conventional immunotherapies. This review summarizes current knowledge on the epidemiology, risk factors, molecular pathogenesis, tumor microenvironment, diagnostic innovations and prognostic biomarkers of UM. We also review novel developments in molecular profiling, liquid biopsy, artificial intelligence-assisted diagnostics, and precision oncology strategies, as well as novel therapeutic approaches such as tebentafusp, protein kinase C inhibitors, immune checkpoint inhibitors, adoptive cell therapies, and liver-directed therapies. These advances are together changing the clinical management of uveal melanoma and provide new opportunities for personalized treatment, earlier detection of metastatic disease and improved patient outcomes.